Sandy Beach from Blue Haven Hotel, Tobago, W.I. - (:unkn) unknown (Y. De Lima and Co., Ltd., Trinidad, 2009)
A picturesque view from a hotel lookout of the ocean and land in the distance which stretches to the mountains. The postcard is addressed to Mr. and Mrs. Strohkarck, Haverford, Pa., U.S.A. Affixed to the postcard is a Venezuelan 35 céntimos stamp, postmarked February 25th, 1971. Postcard number DT-77834-8.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Hotels--Trinidad and Tobago; Ocean--Trinidad and Tobago; 1971; Hospitality industry--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Outdoor furniture--Trinidad and Tobago; Chairs--Trinidad and Tobago; Tables--Trinidad and Tobago; Benches--Trinidad and Tobago; Patios--Trinidad and Tobago; Decks (Architecture, Domestic)--Trinidad and Tobago; Mountains--Trinidad and Tobago; Artillery--Trinidad and Tobago